DECISION ON THE USE OF CLOSE CIRCUIT TELEVISION (CCTV) IN TERMS OF SECURITY, CRIME PREVENTION AND TECHNOLOGY UTILIZATION ( Study on CCTV users in Surakarta city ) - Ida Aryati Dyah; Ratna Putri Saraswatih; Anna Probowati (International Journal of Economics, Business and Accounting Research (IJEBAR), 2021)
Study aims to determine, the partial and the simultaneous influence of security, crime prevention and the use of technology on the decision to use Close Circuit Television (CCTV) in Surakarta City. Types of quantitative descriptive research. The population is all consumers Close Circuit Television (CCTV) In Surakarta with an unlimited number. Sampling techniques using purposive sampling with 100 of respondents. Data analysis techniques are multiple linear regression tests, F tests, t-tests, and R2. Results showed that security, crime prevention and the use of technology had a significant simultaneous and partial effect on the decision to use Close Circuit Television (CCTV) in Surakarta City Keywords: Close Circuit Television (CCTV), security, crime prevention, technology utilization